THE INTERPRETATION OF LITHUANIAN LANGUAGE PROHIBITION UNDER CZARIST OCCUPATION IN “VARPAS” (1889) - TIJŪNĖLIENĖ, ONA (Knygotyra, 2015)
In all times, the status of the Lithuanian language has been associated with the development of Lithuanian state and its people as well as with the changing historical factors. At the end of the 19th century, the intellectuals enshrined the ideas of statehood and freedom. The first Lithuanian newspapers “Aušra” (1883–1886) and “Varpas” (1889–1905) are symbols of the national revival. The aim of this research is to reveal the essence of interpretations published in the newspaper “Varpas” (1889) concerning the language prohibition policy in Lithuania. The “Varpas” trends met the natural expectations of the Lithuanian nation in the end of the 19th century, especially to preserve the native language, while newspaper publishers’ arguments revealed the weakness of the czar’s government strategy regarding the Lithuanian language: Latin letters are connected with the Lithuanian language from the beginning of Christianity in the Lithuania (1387) and the institutional education; the most important criterion for renouncing the Russian alphabet is the nation’s decision. The Latin alphabet is a truly national thing; the prohibition to use the Lithuanian language in public life can be considered as a manipulation of the nation from the religious point of view, as part of the assimilation policy which forces Lithuanians to abandon not only their native language, but also their faith; participation of the church in politics shows its great moral decline. The low national self-awareness of Lithuanian families, scarce examples of a positive relation between the Lithuanian language and Lithuanian intellectuals (medics, priests), students’ receptivity to foreign language elements tattered confidence among Lithuanians. Therefore “Varpas” publishers decided to perform a mission – to explain the ways how to unite, to protect the nation’s foundation – its language, and to strengthen national self-awareness.